Mentoring women in STEM careers: The reciprocal & agentic role of context - Stokes, Paul; Monti, Ileana; Larios, Marina (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2026)
Mentoring discourse has a long history. There are many different approaches to mentoring but most fail to account for the impact that contexts can have on how mentoring is enacted. This is problematic because, without this, it is difficult to properly evaluate the impact of the mentoring itself. We use a case study research design to critically evaluate a recent mentoring intervention, carried out in Arequipa, Peru. Using theories of institutional theory (Paik et al., 2011), power (Clegg 1989), reciprocal mentoring (Haddock-Millar et al., 2024) and agency (Bencherki et al., 2024), we explore the contextual issues at play and develop a framework which explains why there are significant differences in emphasis and focus between mentoring definitions, programmes and initiatives.